SENIOR CITIZENS’ LEARNING AND ACTIVITY IN THE LABOUR MARKET - Rutkiene, Ausra; Lengviniene, Silva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The data provided by Eurostat show that adults who are aged 55 and over participate in education and training about 20 perc. less frequently than the younger ones, who are aged from 18 to 54. Such results are caused by imperfection of adult education, employer attitude and other reasons. Research studies performed in 2004-2006 revealed the problems which arise both for those adults who intend to study and also to educational institutions. Question of the research - which factors cause senior citizens’ motivation to learn aiming at staying active in the labour market? Survey was performed in 2016, 453 respondents participated in the research. The findings show that well-being, economical factors and learning play a decisive role in senior citizens’ staying active in the labour market as well as previous education and place of residence.